A comparative study of advertisement revenue between Malay and English magazine in Malaysia - Hamedi, M.A.; Sarmidi, N.Z.; Mustafa, S.E.; Rahamad, M.S.; Jais, A.W. (Medwell Journals, 2016)
Advertising plays a very important role in determining the survival of the magazine. In addition to editorial content and circulation, advertising revenue will enable the magazine to decide its publishability and marketability. Malay magazine in Malaysia has to compete with magazines in other languages, particularly English and Chinese for a slice in the already small cake of advertising media budget. This study would measure the extent of the differences and similarities in magazine advertising revenue among Malay and English magazine. To that end, four major women's magazine in Malay and English were chosen as sample. Estimation of advertising revenue were made using the rate card of each magazine in addition to data from Media guide and interview from the magazine advertising department. The study shows that although, the circulation of Malay magazine is far higher than English, their advertising revenue is lower. The lower rate of cost-per-thousand (CPM) for Malay magazine in addition to the generally lower quality of readership's demography is contributing to the lack of interest from the advertisers.